2020
DOI: 10.1101/2020.05.07.20094797
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outcomes among HIV-positive patients hospitalized with COVID-19

Abstract: Background: SARS-CoV-2 infection continues to cause significant morbidity and mortality worldwide. Preliminary data on SARS-CoV-2 infection suggests that some immunocompromised hosts experience worse outcomes. We performed a retrospective matched cohort study to characterize outcomes in HIV-positive patients with SARS-CoV-2 infection. Methods: Leveraging data collected from electronic medical records for all patients hospitalized at NYU Langone Health with COVID-19 between March 2, 2020 and April 23, 2020, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
1
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 16 publications
2
63
1
7
Order By: Relevance
“…This is despite no differences in initial chest x-ray findings, presenting symptoms, time of illness onset, prognostic markers such as lymphopenia or elevated D-dimer, or code status. Other case reports and studies have found similarly low morbidity in patients with HIV and SARS-CoV-2 co-infection [ 27 , 28 ]. In our study, the PWH group had very well-controlled disease.…”
Section: Discussionmentioning
confidence: 65%
“…This is despite no differences in initial chest x-ray findings, presenting symptoms, time of illness onset, prognostic markers such as lymphopenia or elevated D-dimer, or code status. Other case reports and studies have found similarly low morbidity in patients with HIV and SARS-CoV-2 co-infection [ 27 , 28 ]. In our study, the PWH group had very well-controlled disease.…”
Section: Discussionmentioning
confidence: 65%
“…HĂ€rter's cohort [26] has a similar mean age but showed higher severity, hospitalization, admission to ICU and mortality rates. However, differences are more difficult to assess with a smaller sample and in the absence of data related to subject comorbidities; the same limitations were found when comparing with the Wuhan [27] and New York [28] , [29] cohorts, both with a significantly higher median age. Finally, we found several similarities in our data with a recent systematic review [30] ; then, we suspect that the differences observed between the different cohorts are probably not significant.…”
Section: Discussionmentioning
confidence: 99%
“…This is tentatively supported by results showing HIV-positive patients with a slight trend towards poorer COVID-19 outcome. [36][37][38] In addition, patients who received haematopoietic stem cell transplantation (HSCT), which leads to profound T-cell lymphopenia, 39 seem to have a worse outcome after SARS-CoV-2 infection, since preliminary data suggest 30% mortality according to an ongoing European Society for Blood and Marrow Transplantation survey. 40 The loss of B cells is less likely to contribute to disease, with patients who are genetically depleted of B cells showing normal outcomes.…”
Section: Discussionmentioning
confidence: 99%